Effect of Government Agricultural Extension Services on Farm Income Among Banana Farmers in Kashenshero Town Council Mitooma District. - Aijuka, Bright (Kabale University, 2024)
This study examined the effect of Government Agricultural Extension Services (GAESs) on farm income among banana farmers. This study utilized a mixed-methods approach to investigate the impact of Government Agricultural Extension Services (GAESs) on farm income among banana farmers. Quantitative data was collected through structured surveys administered to a sample of banana farmers in Kashenshero Town Council, Mitooma District, focusing on variables such as access to extension services, farm income levels, and adoption of agricultural practices. Qualitative data was obtained through in-depth interviews and focus group discussions with farmers, extension workers, and other key stakeholders to explore perceptions and experiences related to the impact of extension services on farm income. The findings revealed a statistically significant positive relationship between access to Government Agricultural Extension Services (GAESs) and farm income among banana farmers in Kashenshero Town Council, Mitooma District. Farmers who had regular access to extension services reported higher farm income compared to those with limited or no access. Qualitative insights further elucidated the pathways through which extension services influence farm income, including improved adoption of agricultural technologies, enhanced crop productivity, and access to market information. Additionally, farmers highlighted the role of extension services in building their capacity and resilience to climate change and other challenges. The findings of this study underscore the significant positive effect of Government Agricultural Extension Services (GAESs) on farm income among banana farmers, Access to extension services facilitates improved agricultural practices, enhances crop productivity, and provides farmers with vital market information, ultimately contributing to higher farm income. Based on the findings, it was recommended that policymakers and stakeholders prioritize investments in agricultural extension services to support smallholder banana farmers. This includes increasing the availability and accessibility of extension services, enhancing the capacity of extension workers, and promoting farmer participation in extension programs, efforts were recommended to tailor extension services to the specific needs and contexts of banana farmers, including addressing gender disparities in access and participation. Additionally, integrating climate-smart agricultural practices and value chain development into extension programs can further enhance their impact on farm income and sustainability.